Characterization of probiotic Bacillus sp. NP5 metabolites and their effect on female catfish broodstock re-maturation - Enzeline, Valensia; Widanarni, Widanarni; Sudrajat, Agus Oman; Alimudin, Alimudin (Indonesian Society of Scientific Aquaculture (ISSA), 2025)
Probiotics are believed to contain active components that influence fish reproduction. This study aimed to evaluate the metabolite compounds present in the probiotic Bacillus sp. NP5 and their effect on female catfish broodstock re-maturation. The first step involved analyzing the metabolite content of the probiotic using liquid chromatography with tandem mass spectrometry (LCMS/MS). Subsequently, feed supplementation with the probiotic was implemented at concentrations of 106 CFU/g (P6), 108 CFU/g (P8), and control (C). Parameters observed included the metabolite content of Bacillus sp. NP5, gonadosomatic index (GSI), hepatosomatic index (HSI), gonad histology, gonad maturity rate, fecundity, number of matured eggs, distribution of egg diameter, fertilization rate (FR), hatching rate (HR), larval survival rate (SR), re-maturation period, and percentage of matured broodstock. The results showed that metabolites such as resveratrol (22.45%) and indoline (7.11%) are likely to influence the fish reproduction directly. Other metabolites, such as oxyresveratrol (22.95%) and vestitol (4.14%), are also thought to play an indirect role in reproduction. The supplementation demonstrated the best reproductive performance at 108 CFU/g treatment, with an increased GSI (14.74%), HSI (1.65%), gonad maturity rate, percentage of mature eggs (86.00%), re-maturation period (4 weeks), percentage of matured broodstock (100%), fecundity (243,605 eggs/broodstock), FR (98.74%), HR (80.62%), and SR (87.31%). The application of probiotic Bacillus sp. NP5 can accelerate re-maturation and enhance reproductive performance of female catfish broodstock. Probiotics contain metabolites that positively affect reproduction and can serve as an alternative to improve reproductive performance in female catfish broodstock. Keywords: Bacillus sp. NP5, female catfish, metabolites, probiotics, re-maturation ABSTRAK Probiotik diyakini mengandung komponen aktif yang berpengaruh terhadap kinerja reproduksi ikan. Tujuan penelitian ini adalah mengevaluasi senyawa metabolit yang terkandung dalam bakteri probiotik Bacillus sp. NP5 dan pengaruhnya terhadap rematurasi induk ikan lele betina. Tahapan pertama adalah analisis kandungan metabolit probiotik Bacillus sp. NP5. dengan metode liquid chromatography with tandem mass spectrometry LCMS/MS. Selanjutnya dilakukan suplementasi pakan dengan perlakuan probiotik pada konsentrasi 106 CFU/g (P6), 108 CFU/g (P8), dan kontrol (K). Parameter yang diamati meliputi kandungan metabolit Bacillus sp. NP5, indeks gonadosomatik (IGS), indeks hepatosomatik (IHS), histologi gonad, tingkat kematangan gonad (TKG), fekunditas, jumlah telur matang, sebaran frekuensi diameter telur, derajat pembuahan (FR), derajat penetasan (HR), sintasan larva (SR), periode rematurasi, dan persentase induk matang gonad. Hasil penelitian memperlihatkan kandungan metabolit seperti resveratrol (22,45%) dan indoline (7,11%) diduga secara langsung berpengaruh terhadap reproduksi. Metabolit lain yang ditemukan seperti oxyresveratrol (22,95%) dan vestitol (4,14%) juga diduga berperan secara tidak langsung. Hasil suplementasi menunjukkan bahwa performa reproduksi terbaik didapat pada perlakuan 108 CFU/g pakan dengan peningkatan nilai IGS (14,74%), IHS (1,65%), TKG, persentase telur matang (86,00%), periode rematurasi (4 minggu), proporsi induk matang gonad (100%), fekunditas (243,605 butir telur/kg bobot induk), FR (98,74%), HR (80,62%), dan SR larva (87,31%). Pemberian probiotik Bacillus sp. NP5 dapat mempercepat rematurasi dan meningkatkan kinerja reproduksi induk ikan lele betina. Probiotik mengandung bahan-bahan metabolit yang berpengaruh positif terhadap reproduksi dan dapat menjadi alternatif dalam meningkatkan performa reproduksi pada induk ikan lele betina. Kata kunci: Bacillus sp. NP5, ikan lele betina, metabolit, probiotik, rematurasi